Motivational and Demotivational Factors Affecting a Teacher’s Decision on Whether to Do Research - Andrej Šorgo; Jasmina Heric (Center for Educational Policy Studies Journal, 2020)
One of the teacher’s basic tasks should be to ensure that the quality of his/her educational work is continually enhanced by the application of practitioner research, as a recognised genre of educational research. The aim of this study was to explore factors that can motivate or demotivate teachers to include research in their educational practice. An online questionnaire was addressed to all Slovenian primary and secondary school teachers and full responses were received from 325 teachers. Although the teachers expressed high perceived self-confidence in their research abilities, this did not transfer to research activity, as only about one quarter of the respondents reported that they performed research. The main drivers of research are an intrinsic motivation for research and career goal orientation, followed by the relatively low influence of important others. Practitioner research is highly valued among teachers, so there must be other factors at work preventing more teachers from starting research activities. Among the leading factors recognised as obstacles are those that can be regarded as facilitating conditions in terms of motivational theory. Work overload, lack of time, school bureaucracy and family life can be regarded as competing with research for the teacher’s time, along with other important issues. The school climate cannot be regarded as the main obstacle to research. The findings call for the reallocation of at least some work duties in favour of research as part of regular employment.